Heaven's interpreters - Reed, Ashley (Cornell University Press, 2020)
Introduction : Writing Women's Religious Agency in Nineteenth-Century America –
Includes bibliographical references and index
Keywords: American fiction; Religion and literature; Women and literature; Women and religion; Fiction